OTORITAS DOSEN DAN HABITUS KEPATUHAN MAHASISWA: KAJIAN TENTANG KEKERASAN SIMBOLIK DALAM RUANG AKADEMIK DI UNIVERSITAS PALANGKA RAYA - Fry Steven; Ririn Ririn; Hamudi Yusuf Ferlianto; Cica (Yayasan Literasi Sains Indonesia, 2026)
Lecturers’ authority within academic spaces functions not only as a means of knowledge transmission but also as a mechanism for shaping students’ habitus of obedience through subtle symbolic practices. Higher education institutions serve as social fields where relations of domination are reproduced through academic legitimacy, evaluation systems, and hierarchical campus culture. This study employs a qualitative case study approach conducted at the Faculty of Social and Political Sciences, Universitas Palangka Raya. Data were collected through participant observation, in-depth interviews, and documentation, and were analyzed using Pierre Bourdieu’s concepts of habitus, capital, field, and symbolic violence. The findings reveal that lecturers’ symbolic domination encourages students to develop adaptive strategies in the form of obedience, behavioral adjustment, and the restriction of critical expression. This habitus of obedience is produced through a continuous process of educational socialization, causing academic domination to be perceived as natural and legitimate. These findings affirm that academic spaces function not only as sites of knowledge production but also as arenas for reproducing power structures through symbolic mechanisms that often remain unnoticed by the actors involved.